2020
DOI: 10.1111/ijag.15252
|View full text |Cite
|
Sign up to set email alerts
|

Integrated photonic materials for the mid‐infrared

Abstract: While silicon photonic integrated circuits for the near-infrared (IR) telecommunication band have attracted great research interest in the past decade, recent advances offer opportunities to extend the operational wavelength to the mid-IR (2.5-20 μm) for free space communications, sensing, environmental monitoring and much more.In this study, we will comprehensively review the current status of materials available for mid-IR waveguides and waveguide integrated photodetectors, with a few application oriented ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 168 publications
(286 reference statements)
0
8
0
Order By: Relevance
“…Nevertheless, a wide range of other materials has been reported, including polymers (i.e., photoresists and Teflon) [57], halides, chalcogenides (i.e., CaF2, NaBr and ZnSe) [28,58], oxides (i.e., alumina, titania and tantala) [59,60], diamond (due to its advantages for quantum photonics) [61,62], or InGaAs [63]. Recently, a review on waveguide materials has been published by Yadav and Agarwal [64].…”
Section: Waveguidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, a wide range of other materials has been reported, including polymers (i.e., photoresists and Teflon) [57], halides, chalcogenides (i.e., CaF2, NaBr and ZnSe) [28,58], oxides (i.e., alumina, titania and tantala) [59,60], diamond (due to its advantages for quantum photonics) [61,62], or InGaAs [63]. Recently, a review on waveguide materials has been published by Yadav and Agarwal [64].…”
Section: Waveguidesmentioning
confidence: 99%
“…Among chip-integrated single-pixel detectors, group IV materials like silicon or germanium or a combination of III-V materials, such as InGaAs, InGaAsSb, InAsSb, PbTe, GaSb, and InP have been used as platforms for NIR and MIR sensing [64,65]. While Si can only absorb up to about 1.1 µm, ion implantation or introducing lattice defects or external agents can improve the detection range of Si-based photodetectors up to 2.4 µm [64]. The entire MIR spectral range can be covered by mercury cadmium telurite (MCT) detectors, which are also most widely used for MIR sensing in bulk spectrometers.…”
Section: Detectors: Single Pixel Arrays Spectrometersmentioning
confidence: 99%
“…In a first integration step, both can be combined into specifically tailored devices with same-wavelength emission and detection from the same active region 13,17,18 , paving the way for a new class of monolithic photonic integrated circuits (PICs) 6,19 . However, in contrast to near-IR PICs with their high degree of maturity 20 , mid-IR (2-20 µm) PICs are still in the early stages of development 21 , and implementing existing integrated photonics solutions remains a challenging task 21,22 . It includes the requirement for new materials 23 and advanced fabrication schemes for developing low-loss and low-dispersion LWIR passive photonic structures on the chiplevel.…”
Section: Introductionmentioning
confidence: 99%
“…However, integrating the detector on-chip is more compact and can improve sensitivity by reducing the volume of active material able to generate thermal noise. Su et al achieved integration of a PbTe photoconductor and demonstrated methane sensing at a wavelength of λ = 3.31 µm [5], but their platform is limited to λ 4 µm due to absorption in the SiO 2 substrate [6] and by PbTe's absorption cutoff [7]. Waveguide-integrated detectors based on narrow-gap 2D materials black phosphorus [8] and tellurene [9] have also been demonstrated, but they too are bandgap-limited to λ 4 µm.…”
mentioning
confidence: 99%
“…While graphene integrated detectors have shown promise at telecom wavelengths [10], the material's advantages are magnified further at longer wavelengths due to the thermal nature of the photothermoelectric (PTE) response mechanism [11,12] and due to the impact of optical plasmon scattering at short wavelengths [13]. Integrated photodetection with graphene has been demonstrated at wavelengths up to 3.8 µm [6] and with chalcogenide glass waveguides [14], but on SiO 2 platforms. To access longer wavelength operation and achieve good sensitivity at zero bias, we introduce a Ge 28 Sb 12 Se 60 (GSSe)-on-CaF 2 waveguide platform supporting gated PTE-based graphene photodetectors.…”
mentioning
confidence: 99%